2020
DOI: 10.1093/carcin/bgaa128
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and prognostic impact of M1 macrophage on esophageal squamous cell carcinoma

Abstract: Macrophages are a double-edged sword with potential cancer-promoting and anti-cancer effects. Controversy remains regarding the effect of macrophages, especially M1 macrophages, on tumor promotion and suppression. We aimed to investigate the role of M1 macrophages in the occurrence and progression of esophageal squamous cell carcinoma (ESCC). Analyzing the data in Gene Expression Omnibus (GEO) database by The CIBERSORT algorithm found that M1 macrophages were one of the important components of many immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Therefore, the failure of CD163+ TAMs to show significant prognostic value in patients in our cohort is not inconsistent with previous studies. Our study supported that high-density invasion of CD11c+ TAMs in the TN region of PT tissues was associated with poorer prognosis in patients with KTs, contrary to many previous studies that confirmed the tumor killing effect of M1 TAMs (36)(37)(38). However, this may also be similar to some previous literature reports that M1 TAMs may play a malignant pro-cancer role in some cancers (39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the failure of CD163+ TAMs to show significant prognostic value in patients in our cohort is not inconsistent with previous studies. Our study supported that high-density invasion of CD11c+ TAMs in the TN region of PT tissues was associated with poorer prognosis in patients with KTs, contrary to many previous studies that confirmed the tumor killing effect of M1 TAMs (36)(37)(38). However, this may also be similar to some previous literature reports that M1 TAMs may play a malignant pro-cancer role in some cancers (39)(40)(41)(42)(43).…”
Section: Discussionsupporting
confidence: 88%
“…EPC1-related immune cells, such as macrophage, B cells, and T cells, may play a role in controlling tumor growth. Furthermore, M1 macrophage was considered to have greater antitumor activity [41], which was positively correlated with EPC1 expression in HPV + tumors. IL2 served as an M1 marker and TNFSF15 was shown to promote M1 production, both of which showed a correlation with EPC1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…We found that compared with normal tissues, the levels of macrophage, myeloid dendritic cell resting and T cell follicular helper in ESCC group were higher, while the levels of B cell, monocyte, CD8+T cell and mast cell activated were lower. Chen et al 28 found that M0 and M1 macrophage were significantly increased in ESCC, and M1 macrophage was involved in inhibiting the invasion and migration of ESCC cells. In large body of experimental evidence has found that M1 macrophage can produce cytokines such as IL1, IL-12 and TNF-α, which produce anti-tumor effect 29 .…”
Section: Discussionmentioning
confidence: 99%